2015
DOI: 10.1007/s12011-015-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the Association of Anemia with the Levels of Zinc, Copper, Iron, Calcium, and Magnesium of Children Aged 6 Months to 3 Years in Beijing, China

Abstract: This study sought to explore the relationship between anemia in children and levels of five minerals in blood. A sample consisted of 242 normal and 304 anemic children paired by sex and age. Hematological parameters were assessed using the Sysmex xs-800i hematology analyzer. Levels of zinc (Zn), copper (Cu), iron (Fe), magnesium (Mg), and calcium (Ca) were measured by polarographic analysis. Differences in these elements between the anemic and normal groups were compared by ANOVA. Relationships between Ca, Zn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Association of Mg with Hb is illustrated in other studies in which Mg deficiency in both animals and humans can result in inflammation and this in turn increases haemolysis (22)(23)(24)(25) . Also, Ca may be associated with Hb: experimental studies showed that supplemental Ca does not interfere with the absorption of Fe if the dose of Ca does not exceeded 800 mg (26)(27)(28) , but if the Ca dose exceeds 1000 mg, it interferes with Fe absorption and may lead to anaemia (29) .…”
mentioning
confidence: 84%
“…Association of Mg with Hb is illustrated in other studies in which Mg deficiency in both animals and humans can result in inflammation and this in turn increases haemolysis (22)(23)(24)(25) . Also, Ca may be associated with Hb: experimental studies showed that supplemental Ca does not interfere with the absorption of Fe if the dose of Ca does not exceeded 800 mg (26)(27)(28) , but if the Ca dose exceeds 1000 mg, it interferes with Fe absorption and may lead to anaemia (29) .…”
mentioning
confidence: 84%